Dietary self‐monitoring and long‐term success with weight management. (13th June 2014) - Peterson, Ninoska D.; Middleton, Kathryn R.; Nackers, Lisa M.; Medina, Kristen E.; Milsom, Vanessa A.; Perri, Michael G.
<x xml:space="preserve">Abstract</x> Objective To examine the contributions of frequency, consistency, and comprehensiveness of dietary self‐monitoring to long‐term weight change. Methods Participants included 220 obese women (mean ± SD, age = 59.3 ± 6.1 years; BMI = 36.8 ± 4.9 kg/m2) who achieved a mean weight loss of −10.39 ± 5.28% from baseline during 6 months of behavioral treatment and regained 2.30 ± 7.28% during a 12‐month extended‐care period. The contributions of cumulative frequency of self‐monitoring (total number of food records), consistency across time (number of weeks with ≥3 records), and comprehensiveness of information recorded were examined as predictors of weight regain in a hierarchical linear regression analysis. The mediating role of adherence to daily caloric intake goals was tested using a bootstrapping analysis. Results The association between high total frequency of self‐monitoring and reduced weight regain was moderated by weekly consistency of self‐monitoring, P = 0.004; increased frequency produced beneficial effects on weight change only when coupled with high consistency (>3 days/week). There was no impact of comprehensiveness on weight change, P > 0.05. The favorable effect of high frequency/high consistency self‐monitoring on weight change was partially mediated by participants' success in meeting daily caloric intake goals (P < 0.001). Conclusion The combination of high frequency plus high consistency of dietary self‐monitoring improves long‐term success in weight management.